2014
DOI: 10.1016/j.nicl.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Altered network properties of the fronto-parietal network and the thalamus in impaired consciousness

Abstract: Recovery of consciousness has been associated with connectivity in the frontal cortex and parietal regions modulated by the thalamus. To examine this model and to relate alterations to deficits in cognitive functioning and conscious processing, we investigated topological network properties in patients with chronic disorders of consciousness recovered from coma.Resting state fMRI data of 34 patients with unresponsive wakefulness syndrome and 25 in minimally conscious state were compared to 28 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
127
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 70 publications
13
127
0
Order By: Relevance
“…34 Brain network topology was assessed through graph theoretical approaches in several studies. 17,20,27 In patients with acute postanoxic coma, fundamental network characteristics were preserved, 27 but a restructuring of hubs (nodes with high degree of connectivity) was noted: anatomical sites that were hubs in HCs were nonhubs in comatose patients. 27 However, patients in MCS and VS showed impaired network properties, such as clustering (connections between the nearest neighbors of a node) and modularity (nodes with higher connections to each other compared with the remainder of the network).…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Brain network topology was assessed through graph theoretical approaches in several studies. 17,20,27 In patients with acute postanoxic coma, fundamental network characteristics were preserved, 27 but a restructuring of hubs (nodes with high degree of connectivity) was noted: anatomical sites that were hubs in HCs were nonhubs in comatose patients. 27 However, patients in MCS and VS showed impaired network properties, such as clustering (connections between the nearest neighbors of a node) and modularity (nodes with higher connections to each other compared with the remainder of the network).…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
“…27 However, patients in MCS and VS showed impaired network properties, such as clustering (connections between the nearest neighbors of a node) and modularity (nodes with higher connections to each other compared with the remainder of the network). 20 One report indicated that scale-free distribution of node size and node degree were absent in patients with VS but maintained in HCs (even under sedation), suggesting that sustained self-organization is a fundamental characteristic distinguishing pharmacologically induced loss of consciousness from DOC. 17 Outcome assessment.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
“…However, at the group level and without correcting for multiple comparisons, the finding of the posterior cingulate cortex/ precuneus and ventromedial prefrontal cortex, pivotal DMN regions, as potential discriminators is in line with earlier structural, functional and metabolic neuroimaging reports. A diffusion tensor imaging-based study showed that DMN integrity might discriminate between VS/UWS and MCS [29], while measuring metabolism and connectivity in DMN-related areas, and especially the posterior cingulate cortex/precuneus, also holds promise [3,5,12]. Future studies should aim to find structural, functional and metabolic biomarkers that could, preferably in a multimodal setup, improve diagnosis at the single subject level.…”
Section: Vs/uws Vs Mcsmentioning
confidence: 99%
“…With task-free neuroimaging, an examiner is not dependent on patient co-operation and a patient's possibility to exhibit body movement. In resting state fMRI, examination of intactness of the default mode network (DMN) might improve diagnosis in DOC, as it is known to be important for internally-oriented consciousness [5,[7][8][9][10][11][12]. In recent years, interest has also increased for other brain regions associated with specific higher-order networks [13].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies showed the important role of thalamus. Crone et al (2014) investigated brain network properties in DOC patients and identified alterations between normal controls and patients on a global level but also in the fronto-parietal and thalamus networks, while only the precuneus area showed differences between patient groups. It is noted that the level of consciousness is correlated with the disruption in the precuneus, medial, and frontal regions.…”
Section: Introductionmentioning
confidence: 99%